Integrated nutrient supply and seed rate for direct seeded rainfed upland rice (Olyza sativa) in mid hills of Himachal Pradesh* - MANKOTIA, B S; SHEKHAR, J (The Indian Journal of Agricultural Sciences, 2011)
In Himachal Pradesh, rice (Oryza sativa L.) is grown manure (2 : 1) and turning green manure at 25 days after under various topo-sequences ranging from uplands to sowing + 50 % recommended fertilizer dose; T,, line sowing lowlands at varying elevations covering an area of 78 000 ha (80 kg seedha) + recommended fertilizer dose + 5 tonnes and the average rice productivity of the state is 1 960 kg/ha............